COORDINATION OF MOBILE-ROBOT SYSTEM WITH BEHAVIOR-BASED ARCHITECTURE - Andi, Andi (Reviewer, 2018)
In this paper we propose an algorithm for coordinating a group of mobile robots that go through predeï¬ned paths in a dynamic industrial workplace. The coordination is characterized by a decoupled approach. Then, a behavior-based architecture be used as the underlying control representation providers a useful encoding that lends robustness to control. Some robot behaviors be designed to support for accomplishing industrial task. Four Lego Mindstorms robots used to implement the proposed algorithm. This research tackles the coordination movement issue in material handling in order to minimize the delivery time. Several experiment have been done to know performances of the system. The promising results have been proved that the proposed control architecture has better capability to accomplish useful task in real industrial-like environment.